2001
DOI: 10.1046/j.1528-1157.2001.081420.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pediatric Epilepsy on the Family: A New Scale for Clinical and Research Use

Abstract: Summary:Purpose: There is no brief, global instrument available that specifically measures the psychosocial impact of pediatric epilepsy on the family. An 11-item scale was created for parents' use to evaluate the influence of epilepsy on the major aspects of their family and child's life. This will be a helpful tool both in the clinical setting and as an outcome measure for research studies.Methods: Mothers rated their child's quality of life on a visual analogue scale (1-6) and completed the Impact of Pediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
99
1
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(116 citation statements)
references
References 27 publications
(20 reference statements)
7
99
1
3
Order By: Relevance
“…Stigma, reduced quality of life, and greater psychosocial impact in children with epilepsy have been associated with disordered behaviour. 43,44 In our study, behavioural disorders alone caused school exclusion in 12% of those children who were not attending school regularly. Other factors affecting school attendance in this population are currently being investigated.…”
mentioning
confidence: 51%
“…Stigma, reduced quality of life, and greater psychosocial impact in children with epilepsy have been associated with disordered behaviour. 43,44 In our study, behavioural disorders alone caused school exclusion in 12% of those children who were not attending school regularly. Other factors affecting school attendance in this population are currently being investigated.…”
mentioning
confidence: 51%
“…GASE has adequate content, convergent, and construct validity and high intra-and interrater reliability. 13 They also rated comorbidities using single items adapted from previous studies, 14 specifically, any behavior (0 ϭ none to 3 ϭ severe) or cognitive problems (0 ϭ none to 4 ϭ severe). The classifications of the International League Against Epilepsy 15,16 guided the categorization of neurologists' reports of epilepsy/epilepsy syndrome types.…”
Section: Epilepsy Characteristicsmentioning
confidence: 99%
“…In adults, epilepsy has a negative impact on profession, marriage, general and mental health. In childhood, it affects the physical and cognitive health of the child and his psychosocial adjustment 6,7 . Studies on the psychosocial impact of children's epilepsy have shown an association between emotional and behavioral problems and the disease 8 .…”
mentioning
confidence: 99%
“…In teenagers, the consequences might be even more negative, since this period of life is marked by significant changes 4 . With the purpose of evaluating QOL of epileptic patients, many instruments (for adults and children), general and specific for epilepsy, have been used 6,7,[9][10][11][12] . A common finding from these evaluations is that refractory epilepsy is a condition that impacts directly and negatively on the QOL of the patients, mostly worsening social integration 3 .…”
mentioning
confidence: 99%